C-glycosides incorporating the 6-methoxy-2-naphthyl moiety are selective inhibitors of fungal and bacterial carbonic anhydrases - Riafrecha, Leonardo Ezequiel (2015)
A small series of C-glycosides containing the methoxyaryl moieties was tested for the inhibition of the β-class carbonic anhydrases (CAs, EC 4.2.1.1) from Cryptococcus neoformans and Brucella suis. Many compounds showed activities in the micromolar or submicromolar range and excellent selectivity for pathogen CAs over human isozymes. The deprotected glycosides incorporating the 6-methoxy-2-naphthyl moiety showed the best inhibition profile and therefore represent leads for the development of novel anti-infectives with a new mechanism of action.